2022
DOI: 10.3389/fneur.2022.957709
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion effect of the leo braided stent for aneurysms in the posterior and distal anterior circulations: A multicenter cohort study

Abstract: Background and purposeThe treatment of aneurysms located in the posterior and distal anterior circulations remains a challenge. Leo stents with a flow diversion (FD) effect may be a potential option, which needs to be clearly studied.MethodsFrom January 2016 to October 2021, 133 patients with 145 aneurysms in the posterior and distal anterior circulations, treated with Leo stents, were retrospectively analyzed in three neurosurgical centers. Data on demographic information, aneurysm characteristics, procedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Leo stent has been indicated for intracranial aneurysm, but it has also been reported to be used in a few case reports of VBD besides enterprise and Solitaire. [7][8][9] Besides using multiple Leo stent, nondominant vertebral artery occlusion was also performed to reduce the blood flow into the space between the stents and the vascular wall, which can further improve the hemodynamics of the VBD. The occlusion should be performed as distal vertebral artery as possible to prevent occlusion of posterior inferior cerebellar artery and anterior spinal artery, but not to distal to obstruct This combination of technique has been reported as well in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Leo stent has been indicated for intracranial aneurysm, but it has also been reported to be used in a few case reports of VBD besides enterprise and Solitaire. [7][8][9] Besides using multiple Leo stent, nondominant vertebral artery occlusion was also performed to reduce the blood flow into the space between the stents and the vascular wall, which can further improve the hemodynamics of the VBD. The occlusion should be performed as distal vertebral artery as possible to prevent occlusion of posterior inferior cerebellar artery and anterior spinal artery, but not to distal to obstruct This combination of technique has been reported as well in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, progressive occlusion of a “significant proportion” of coiled aneurysms and diminished recanalization rates have been proposed as proxies for the flow diversion effect of a stent [ 9 , 14 , 22 ]. Consequently, in this study, to investigate the flow diverter effects of different types of stents, aneurysms were divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Braided stents (BS) are suggested to have flow-diverting properties [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, the presence of this effect has been disputed by some authors [ 11 , 12 , 13 ], and if such a flow diversion property exists at all, its extent has remained unknown to date [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… 21) Another recent report showed that the rates of complete occlusion, permanent morbidity, and mortality were 90.4%, 2.0%, and 0%, respectively. 22) Neck-bridging stents or SAC continue to advance, leading to the development of novel therapeutic devices.…”
Section: Stent-assisted Coilingmentioning
confidence: 99%